FISH COMMUNITY STRUCTURE IN DIFFERENT SEAGRASS BEDS OF BARRANG LOMPO ISLAND - Rohani Ambo Rappe (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2010)
The importance of seagrass meadows as a habitat for fishes, including several of economic importance, is widely acknowledged. The complexity of seagrass beds might offer a different condition of habitat for fishes. The physical nature of the seagrass canopy is thought to play a major role, potentially influencing available shelter, food, and protection from predators. Structural complexity of seagrass such as shoot and leaf density is also an important factor in determining ecological function of seagrass in the marine environment. The objective of the research is to assess the ecological function of different seagrass beds (in terms of spesies and density) in supporting fish community. The study found 28 species of fish originating from 14 families and Pomacentridae were dominantly found. Abundance of fish found to be higher in seagrass beds with high densities both composed by one species of seagrass (monospesific) or by more than one species of seagrass (multispesific), compared to the seagrass beds with low density and bare areas. Fish community diversity index was found higher in dense seagrass beds composed of many species of seagrass compared to the rare and consists of only one species of seagrass. The presence of epiphytes as nutrients for the fish that live in seagrass beds may contribute to the finding.Keywords: Seagrass, fish, Barrang Lompo Island